California's redwood forest - Mihaly, Christy (Natural wonders of the world (Focus Readers (Firm)), 2018)
Highlights the history of California's Redwood Forest from its geological formation to the vegetation and animal life found there. Includes text-related questions, a glossary, resources for further information, and color photographs.